Paragorgia arborea - Schejter, L.; Genzano, G.; Pérez, C. D.; Acuña, F.; Cordeiro, R. T. S.; Silva, R. A.; Garese, A.; Bremec, C. S. (Zenodo, 2020)
Paragorgia arborea (Linnaeus, 1758) Material examined: BBB 2016: St. 13. Distribution: Western North Atlantic, East Canada to Cape Hatteras; Boreal Eastern Atlantic, northern Mid-Atlantic Ridge; Lusitanian-Mediterranean (Watling & Auster 2005); Norway to Nova Scotia, including Faroes Islands, Iceland and Greenland, 1330 m (Tendal 1992); off Crozet Islands, Indian Ocean (46°05’– 46°24.1’S, 49°37.0’– 50°37.1’E, 140–270 m) (Grasshoff 1979; D’Ambrosio et al. 1984); Aleutian Islands (Heifetz et al. 2005); Makarov Bay, Iturup Island, Sea of Okhotsk (Nedashkovskaya et al. 2005); Southern California (52°17’– 52°22’N, 160°40’– 160°34’E, 659–798 m), New Zealand (33°55’36”S– 52°17’22”S, 159°40’00– 177°54’30”E, 659–1525 m) (Sánchez 2005); Off Patagonia and Malvinas Islands (40°57’– 54°38’S, 56°52’– 63°00’W, 340– 1000 m) (Grasshoff 1979); Burdwood bank (54°31´S, 62°11´W, 330 m) (as Paragorgia sp.) (Auscavitch & Waller 2017); Drake Passage, 57°04´S, 67°30´W, 1400 m (as Paragorgia sp.) (Waller & Robinson 2011); off Staten Island (608 m) (present study). Remarks: According to Sánchez (2005), this species has a disjunct distribution between the Arctic and Antarctic, with no linking records. Auscavitch & Waller (2017) and Waller & Robinson (2011) cited Paragorgia sp. for the Drake passage and Burdwood bank, their identification at genus level is justified since the samplings were made by towed camera surveys. Deichmann (1936) said that according to Verrill (1922) this species is common off the fishing banks off Nova Scotia and Newfoundland. Published as part of Schejter, L., Genzano, G., Pérez, C. D., Acuña, F., Cordeiro, R. T. S., Silva, R. A., Garese, A. & Bremec, C. S., 2020, Checklist of Benthic Cnidaria in the SW Atlantic Ocean (54 ºS- 56 ºS), pp. 201-239 in Zootaxa 4878 (2) on page 222, DOI:10.11646/zootaxa.4878.2.1, http://zenodo.org/record/4424884